Nutrient uptake of the diploid potato (solanum phureja) variety criolla colombia, as a reference point to determine critical nutritional levels (2012)
In the production costs of in the diploid potato var. Criolla Colombia, fertilizer represents 17% of the total costs, and it’s inappropriate and sometimes excessive use translates into expensive investments with technical inefficiency. This is mainly due to a lack of nutrient absorption levels of the selected variety. The research was conducted in Granada (Colombia) with five fertilization treatments (absolute control, commercial control, technical recommendation + 50%, technical recommendation and technical recommendation - 50%) arranged in a randomized complete block design with three replications. We evaluated dry matter, nutrient uptake, yield and specific gravity. The analysis showed that the most important elements were N, P, K, Ca, Mg, Zn, B and S, with higher absorption in the 113 days after planting (dap) with the commercial control, technical recommendation + 50% and technical recommendation, from highest to lowest. There were no statistically significant differences in yield for commercial control, technical recommendation + 50% and technical recommendation, but the economic analysis showed that the critical level of fertilization was found in commercial control.